(Ethylenediamine-κ2N,N)bis[2-(pyridin-2-yl-κN)-1,3-imidazol-1-ido-κN1]cobalt(III) nitrate monohydrate - Xiu-Ling Feng (Acta Crystallographica Section E, 2012)
In the title compound, [Co(C8H6N3)2(C2H8N2)]NO3·H2O, the CoIII ion is coordinated by four N atoms from two 2-(pyridin-2-yl)-1,3-imidazol-1-ide ligands and two N atoms of ethylenediamine in a distorted octahedral geometry. In the crystal, classical N—H...N(O) and O—H...N(O) hydrogen bonds connect all the isolated components together to yield a three-dimensional structure.